Organizational Culture and Quality Management Practices in the Hospital Sector - Sousa, Sergio (Journal of Reviews on Global Economics, 2019)
Research in the healthcare sector is a particular relevant topic as a contribution to the development of patient care service improvement. This research focuses the identification and understanding of the organizational culture dimensions and its relation with the quality management practices in the hospital sector. A case-based research was implemented in two major public hospitals, with quantitative and qualitative methods, through multivariate and thematic analysis. Our findings allows us to postulate that the existence and intensity of a particular set of organizational culture dimensions was a catalyst factor of different realities in the implementation and development of the quality management systems in those hospitals. We believe that we were able to reach valid advice for practitioners, and also ensuring a contribution to knowledge, reinforcing the value of the contingency approach to quality management and taking relevant steps towards theory building about the links between organizational culture and quality management in the healthcare services, particularly in the hospital sector.